Pembelajaran Bahasa Inggris Berbasis Lagu Anak-Anak Untuk Pengembangan Vocabulary - Candra Kirana; Wan Azura; Irasari Irasari (Journal of Sustainable Education, 2026)
Learning English for early childhood requires engaging, interactive, and enjoyable methods to help students understand and remember new knowledge more easily. One effective learning medium is English children's songs. Songs are characterized by simple lyrics, repeated words or phrases, and memorable rhythms, which can help students master English. Furthermore, the use of songs can create a more active and engaging learning environment. This study aims to determine the effect of using children's songs on improving students' English comprehension. The research method used was a descriptive qualitative approach, with data collection techniques including observation and interviews. The results indicate that the use of English children's songs has a positive impact on the learning process. Songs can increase students' interest and motivation to learn, simplify the process of remembering new vocabulary, and create a fun learning environment, thus supporting the improvement of English comprehension in early childhood.